2015
DOI: 10.1209/0295-5075/111/10002
|View full text |Cite
|
Sign up to set email alerts
|

Strong anomalous diffusion of the phase of a chaotic pendulum

Abstract: In this letter we consider the phase diffusion of a harmonically driven undamped pendulum and show that it is anomalous in the strong sense. The role played by the fractal properties of the phase space is highlighted, providing an illustration of the link between deterministic chaos and anomalous transport. Finally, we build a stochastic model which reproduces most properties of the original Hamiltonian system by alternating ballistic flights and random diffusion.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 43 publications
1
4
0
Order By: Relevance
“…Remarkably, these non-universal distributions, which feature non-analytic behaviors, are obtained from the general principle of single big jump, which provides a unique physical explanation of the process driving the rare events. Finally, we also derive the scaling of all the moments of the distribution that, interestingly, feature strong anomalous diffusion [28][29][30]. All our analytical results are in very good agreement with extensive numerical simulations.…”
Section: Introductionsupporting
confidence: 58%
See 1 more Smart Citation
“…Remarkably, these non-universal distributions, which feature non-analytic behaviors, are obtained from the general principle of single big jump, which provides a unique physical explanation of the process driving the rare events. Finally, we also derive the scaling of all the moments of the distribution that, interestingly, feature strong anomalous diffusion [28][29][30]. All our analytical results are in very good agreement with extensive numerical simulations.…”
Section: Introductionsupporting
confidence: 58%
“…In Figure 5 we consider the super-diffusive regime α > 1, ν > α/2 and ν > η. In panel (a) we plot R q (T ) and in panel (b) we plot the function γ(q) , that shows strong anomalous diffusion [28,29]. Far away from the transition where preasymptotic effects are expected to be stronger, simulations displays a nice agreements with theoretical values:…”
Section: The Moments Of the Distributionmentioning
confidence: 76%
“…This in turn implies that the single jump is needed, at least in some cases, for the investigation of the mean square displacement of the spreading process, which is easily considered the main quantifier of diffusion. Since strong anomalous diffusion is observed in a wide range of systems, we believe the principle of large jump has wide spread applications [57][58][59][60][61].…”
Section: Discussion and Open Problemsmentioning
confidence: 99%
“…For example, in piecewise linear one-dimensional chaotic maps it has been found that the diffusion coefficient is a fractal function of control a e-mail: s.gilgallegos@qmul.ac.uk b e-mail: r.klages@qmul.ac.uk c e-mail: janne@solanpaa.fi d e-mail: esa.rasanen@tut.fi parameters [4,5,6]. A relatively simple two-dimensional map with similarly irregular diffusion coefficients is the standard map [7,8], which can be derived as a time discrete version of a chaotic nonlinear pendulum equation [9,10]. Here it has been observed that normal diffusion is interrupted by regions in parameter space which are related to accelerator modes yielding superdiffusive transport [11,12,13].…”
Section: Introductionmentioning
confidence: 99%